2012
DOI: 10.1099/vir.0.041871-0
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic banana plants expressing small interfering RNAs targeted against viral replication initiation gene display high-level resistance to banana bunchy top virus infection

Abstract: The banana aphid-transmitted Banana bunchy top virus (BBTV) is the most destructive viral pathogen of bananas and plantains worldwide. Lack of natural sources of resistance to BBTV has necessitated the exploitation of proven transgenic technologies for obtaining BBTV-resistant banana cultivars. In this study, we have explored the concept of using intron-hairpin-RNA (ihpRNA) transcripts corresponding to viral master replication initiation protein (Rep) to generate BBTV-resistant transgenic banana plants. Two ih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…The accessible gene pool available for GM is significantly broader than that available to conventional banana breeders and, as a result, genes for resistance to BBTV and BXW have already been identified [44][45][46][47]. Further, genes from M. balbisiana are available for use in genetic modification, as there is no possibility of transferring BSV genes [48].…”
Section: Conventional Breeding or Genetic Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The accessible gene pool available for GM is significantly broader than that available to conventional banana breeders and, as a result, genes for resistance to BBTV and BXW have already been identified [44][45][46][47]. Further, genes from M. balbisiana are available for use in genetic modification, as there is no possibility of transferring BSV genes [48].…”
Section: Conventional Breeding or Genetic Modificationmentioning
confidence: 99%
“…The majority of these studies have been reports from a glasshouse evaluation and therefore, it is difficult to determine whether they only represent experimental projects, or whether they are part of a program to progress to field trial, and ultimately, to general release. The most targeted traits have been pest and disease resistance, abiotic stress tolerance, and fruit ripening, and these have included resistance to BBTV using RNAi (RNA interference) [44,59], resistance to Fusarium wilt race 1 using anti-apoptosis genes [60], RNAi [61] or a defensin gene [62], resistance to nematodes using plant-derived or synthetic peptides [63], and the over-expression of a banana-derived WRKY transcription factor to alter abiotic responses [64]. These reports, in addition to a number of others, have used a range of banana genes, RNAi constructs derived from banana pathogens, or genes not derived from bananas.…”
Section: The Progress With Genetically Modified Bananasmentioning
confidence: 99%
“…Two Indian research groups have claimed success. Shekhawat et al (2012) have published an account of tests that showed that transformed 'Rasthali' (AAB genome, syn. 'Silk') did not develop symptoms when exposed to aphids carrying BBTV.…”
Section: Recent Bbtv Resistant Banana Clone Development Through Rnai mentioning
confidence: 99%
“…Grand Nain, Virupakshi (Hill banana), Robusta, Nendran, Rasthali, Poovan, Ney Poovan, Monthan and Red Banana are severely affected by BBTD. There is no resistance gene source available in germplasm of bananas and plantains (Shekhawat et al, 2012). The BBTV affected plants show intermittent dark green dots, dash, streaks of variable length on leaf sheath, midrib, leaf veins and petioles of infected plants.…”
Section: Introductionmentioning
confidence: 99%